Pembentukan Karakter Peserta Didik Melalui Implementasi Program Mengaji Pagi Di MA Almasa Kalipang Grati - Hamid Ridwan, Yuniar Mujiwati (Al-Makrifat: jurnal kajian Islam, 2020)
The purpose of this study determined the implementation of the Morning Kaji Program. Based on the condition of education in Indonesia the school has started Morning Kaji activities. The Morning Kaji Program is designed to build character for students at MA Almasa Kalipang School. This program starts from 06:30 to 07:00. In the Morning Kaji Program, it is hoped that it can create an ideal educational environment and give birth to people who will be the driving forces for social, political, economic, and religious life. This study used qualitative research, the action chosen in the reciting process is that students are given material that is contained in the meaning of the Qur’an because from this it can change the character of a student, in this case, students usually pay attention to the principles that differentiate the meaning. in the recitation of the Qur’an, because every meaning in the Qur’an is the firm of Allah which does have a lot of meaning for our lives, that is why the Morning Qurâ€™ran Program is very important for character building. The data collection techniques use interviews, observations, documentation. The results of this study indicate that the implementation of the Morning Kaji Program in the Character Building of Students at MA Almasa Kalipang Tengah Grati Pasuruan has been done optimally, this can be seen in 1) Implementation of the Morning Kaji Program in Forming the Character of Students at MA Almasa Kalipang Tengah, Grati Pasuruan, 2) Obstacles in the Implementation of the Morning Kaji Program in Character Building, 3) Solutions in the Implementation of Character Education through the Implementation of the Morning Kaji Program.